Antral follicles population in heifers and cows of Nelore and Girolando breeds - Jair Sábio de Oliveira Junior (Semina: Ciências Agrárias, 2015)
The aim of this study was to evaluate ovarian antral follicle populations (OAFP) of Nelore and Girolando breed heifers (12–18 months old) and cows (24–60 months old). Animals were assigned to four groups: (1) Nelore cows (n = 18), (2) Girolando cows (n = 20), (3) Nelore heifers (n = 7), and (4) Girolando heifers (n = 7). Cows were treated to synchronize follicular wave emergence by implantation of an intravaginal device containing 1.9 g of progesterone, as well as intramuscular administration of 2 mg of estradiol benzoate and 25 mg of dinoprost. This synchronization treatment was administered at a random day of the estrous cycle of each cow, designated D0. Intravaginal devices were removed on D7, and on D11, OAFP counts were performed by transvaginal ovarian ultrasound. For each cow, all follicles ?3 mm in diameter were counted in both ovaries and counts were performed three times at 35-day intervals. Counts were also obtained from heifers, but these animals were not treated for synchronization of follicular wave emergence. Analysis of variance (ANOVA) with Tukey’s test and Pearson’s correlation test were used to compare mean OAFPs between counts as well as mean OAFPs between breed and age groups. No differences were observed in mean OAFPs between Nelore and Girolando cows (30.9 vs. 26.7, respectively; P > 0.05) or heifers (16.2 vs. 18.1, respectively; P > 0.05). However, within each breed, there were differences in mean OAFPs between heifers and cows (for Nelore cattle: 16.2 and 30.9, respectively; for Girolando cattle: 18.1 and 26.7, respectively; both P < 0.05). In conclusion, OAFPs were similar between Nelore and Girolando breeds and were influenced by age. Furthermore, we observed a high correlation for individual animals between the mean numbers of follicles counted in both ovaries and total number of follicles counted in either the right or left ovary, indicating that the evaluation of a single ovary is sufficient to estimate the OAFP of an individual.